Transposition of the great arteries and narrowing of the aortic arch. Emphasis on right ventricular characteristics. - Moene, R J (1985)
Of 279 patients with transposition of the great arteries, 14(5%) had narrowing of the aorta, including local coarctation (6), isthmus hypoplasia (6), isthmus atresia (1), and kinking of the aorta (1). There were six deaths in 10 surgically treated patients; in addition four patients died before operation. Two of the four survivors had a subpulmonary malalignment ventricular septal defect with angiocardiographic narrowing of the right ventricular outflow tract, two had evidence of redundant muscle tissue obstructing the right ventricular outflow tract. Necropsy showed the presence of anatomical right ventricular outflow tract or inflow tract obstruction or both in all 10 cases. Outflow tract obstruction was represented by anterior displacement of the infundibular septum and ventriculoinfundibular fold (in hearts with a subpulmonary malalignment ventricular septal defect) or by redundant muscle tissue; inflow tract obstruction was represented by hypoplasia of the tricuspid valve. It is concluded that the combination of transposition of the great arteries and narrowing of the aorta is always accompanied by right ventricular outflow or inflow tract obstruction or both; the right ventricular abnormalities are probably responsible for the presence of the aortic arch anomalies by reducing aortic flow during morphogenesis. Successful surgical treatment of this complex anomaly is feasible in selected cases.